A novel amino acid and metabolomics signature in mice overexpressing muscle uncoupling protein 3. Issue 2 (10th November 2016) - Aguer, Céline; Piccolo, Brian D.; Fiehn, Oliver; Adams, Sean H.; Harper, Mary‐Ellen
ABSTRACT: Uncoupling protein 3 (UCP3) is highly selectively expressed in skeletal muscle and is known to lower mitochondrial reactive oxygen species and promote fatty acid oxidation; however, the global impact of UCP3 activity on skeletal muscle and whole‐body metabolism have not been extensively studied. We utilized untargeted metabolomics to identify novel metabolites that distinguish mice overexpressing UCP3 in muscle, both at rest and after exercise regimens that challenged muscle metabolism, to potentially unmask subtle phenotypes. Male wild‐type (WT) and muscle‐specific UCP3‐overexpressing transgenic (UCP3 Tg) C57BL/6J mice were compared with or without a 5 wk endurance training protocol at rest or after an acute exercise bout (EB). Skeletal muscle, liver, and plasma samples were analyzed by gas chromatography time‐of‐flight mass spectrometry. Discriminant metabolites were considered if within the top 99th percentile of variable importance measurements obtained from partial least‐squares discriminant analysis models. A total of 80 metabolites accurately discriminated UCP3 Tg mice from WT when modeled within a specific exercise condition (i.e., untrained/rested, endurance trained/rested, untrained/EB, and endurance trained/EB). Results revealed that several amino acids and amino acid derivatives in skeletal muscle and plasma of UCP3 Tg mice ( e.g ., Asp, Glu, Lys, Tyr, Ser, Met) were significantly reduced after an EB; that metabolites associated with skeletal muscle glutathione/Met/Cys metabolism (2‐hydroxybutanoic acid, oxoproline, Gly, and Glu) were altered in UCP3 Tg mice across all training and exercise conditions; and that muscle metabolite indices of dehydrogenase activity were increased in UCP3 Tg mice, suggestive of a shift in tissue NADH/NAD + ratio. The results indicate that mitochondrial UCP3 activity affects metabolism well beyond fatty acid oxidation, regulating biochemical pathways associated with amino acid metabolism and redox status. That select metabolites were altered in liver of UCP3 Tg mice highlights that changes in muscle UCP3 activity can also affect other organ systems, presumably through changes in systemic metabolite trafficking.—Aguer, C., Piccolo, B. D., Fiehn, O., Adams, S. H., Harper, M.‐E. A novel amino acid and metabolomics signature in mice overexpressing muscle uncoupling protein 3. FASEB J. 31, 814–827 (2017). www.fasebj.org